Neutralization of Streptolysin S-Dependent and Independent Inflammatory Cytokine IL-1β Activity Reduces Pathology During Early Group A Streptococcal Skin Infection - Flaherty, Rebecca A.; Donahue, Deborah L.; Carothers, Katelyn E.; Ross, Jessica N.; Ploplis, Victoria A.; Castellino, Francis J.; Lee, Shaun W. (Frontiers in Cellular and Infection Microbiology, 2018)
The bacterial pathogen Group A Streptococcus (GAS) has been shown to induce a variety of human diseases ranging in severity from pharyngitis to toxic shock syndrome and necrotizing fasciitis. One of the major virulence factors produced by GAS is the peptide toxin Streptolysin S (SLS). Though this toxin has long been recognized as a potent cytolysin, recent evidence from our lab has indicated that SLS-dependent cytotoxicity in keratinocytes is mediated through inactivation of the cytoprotective factor Akt1 and subsequent activation of the pro-inflammatory mediators p38 MAPK and NFκB. Initiation of this cascade ultimately leads to cell death through a form of programmed necrosis, which is dependent on RIPK1 and RIPK3. These findings led us to hypothesize that activation of p38 MAPK and NFκB signaling drive the production of pro-inflammatory cytokines which, in turn, serve as positive feedback signals to initiate programmed necrosis in infected host cells. To address this hypothesis, we utilized a cytokine array to characterize the SLS-dependent pro-inflammatory cytokine response to GAS infection in human keratinocytes. From these studies, IL-1β was found to be markedly upregulated in the presence of SLS, and further investigation revealed that this cytokine contributes to cytotoxicity in human keratinocytes during infection. Subcutaneous infection studies were performed in mice to address the physiological impact of increased IL-1β production. These studies demonstrated that IL-1β is produced during GAS skin infection in an SLS-dependent manner. Furthermore, inhibition of this cytokine and the upstream kinases and other signaling mediators that drive its production reduced SLS-mediated lesion formation early in the infection process. Together, our findings indicate that pharmacological inhibition of this inflammatory axis holds promise as a therapeutic strategy to reduce tissue destruction during severe invasive Group A Streptococcal infections.